Child Participation in Family-School Cooperation - Maleš, Dubravka (Array, 2014)
The paper discusses the cooperation between family and school from the perspective of the UN Convention on the Rights of the Child (1989). Given that the principal purpose of the cooperation between family and school is the child’s well-being, it is reasonable to expect the child’s participation in the situations of direct parent-teacher cooperation. The theoretical part of the paper is grounded on the contemporary scientific findings in family-school cooperation and the role of the child in the process, while the empirical part of the paper seeks to answer whether the requirement for child participation is being fulfilled in family-school cooperation in Croatia. As a theoretical basis for the research, Hart’s (1995) ‘Ladder of Participation’ model has been used, whereas the results can serve as guidelines for improving the existing school practices and introducing changes in school legislation relating to the cooperation with parents.